The Relationship Between Social Media Addiction and Self-Esteem in Medical Students of Diponegoro University - Subiyakto, Difa Maulana; Saktini, Fanti; Sumekar, Tanjung Ayu (Diponegoro International Medical Journal, 2024)
Background: In the modern era, social media has become a necessity in carrying out daily activities. Playing social media too often can have negative effects. These negative effects include addiction. Social media addiction can interfere with daily activities and affect the level of self-esteem.Objective: To prove the relationship between social media addiction and selfesteem among medical students at Universitas Diponegoro.Methods: This research was an analytical observational investigation utilizing a cross-sectional methodology. The study was carried out over a span of one month, involving 90 participants from the medical students batch 2022 at Universitas Diponegoro. The  questionnaires used were the Social Media Addiction Scale-Student Form (SMAS-SF) and Rosenberg Self Esteem Scale (RSES). The assessment of the correlation between social media addiction and self-esteem using the Spearman test.Results: 2.2% of respondents had a very low level of social media addiction; 52.2% had a low level; 44.4% had a high level; and 1.1% had a very high level. In terms of self-esteem, the data revealed that 84.4% of respondents had a high level of self-esteem, while 15.6% had a low level. In the correlation test between demographic factors, social media addiction, and self-esteem,  an insignificant relationship was found with a p-value greater than 0.05. Meanwhile, a significant relationship was found in the correlation test between social media addiction and the level of self-esteem (p=0.001, r=-0.335).Conclusion: A significant relationship exists between social media addiction and the level of self-esteem among medical students at Diponegoro University.